STUDENTS’ PERCEPTIONS OF TEACHERS’ OWN-LANGUAGE USE: A CASE STUDY IN AN INDONESIAN EFL SENIOR HIGH SCHOOL - Wulandari Santoso (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2019)
The dominant position of the monolingual approach in English language teaching has been questioned and the incorporation of students’ own language has been increasingly encouraged. This study investigated students’ perceptions of the desirability of teachers’ own language-use and their views regarding for what purposes teachers should use students’ own language in an immersion senior high school in Indonesia. This case study used a sequential explanatory design, gathering quantitative data from questionnaires to 89 students and qualitative data from semi-structured interviews to 4 students. The findings of this research revealed that the students’ perceptions were complex because although English was expected to be mainly used, many of the students wanted the teachers to use the own language for language-related purposes, classroom management purposes, and affective purposes. The main pedagogical implication of this study calls for bi/multilingual education in this context. Further research may explore the impacts of the monolingual approach and the power of English language on students’ identities in Indonesia.